The Use of the Oswestry Disability Index (ODI) and Nordic Body Map (NBM) in the Assessment of Low Back Pain Among Office Employees - Suryadinata, Rivan Virlando; Pande, Gek Made Cempaka Priyanka (Journal of Nursing Science Update (JNSU), 2025)
Low back pain is a common health problem experienced by office workers. Poor posture and ergonomic habits can result in low back pain. Low back pain can be assessed using the Oswestry Disability Index (ODI) and Nordic Body Map (NBM) questionnaires. Different assessment results for individual workers can lead to delays in early detection and treatment, which can reduce productivity. This study aims to determine the differences between the ODI and NBM in assessing low back pain (LBP) in office employees. The research method used was observational with a cross-sectional design. The respondents were office workers aged 25–60 years with no history of spinal trauma. The study included 120 participants, selected using purposive sampling. The assessment was carried out using ODI and NBM questionnaires. Furthermore, a chi-square test will be used to analyze the data obtained and determine the difference in the assessments of the two questionnaires. The results indicate no significant difference between the two questionnaires' ratings (p=0.142). Therefore, it can be concluded that the two questionnaires are similar in their assessment of the risk of low back pain in office workers, although several factors remain unassessed.